Circulating microRNAs as biomarkers - True Blood? - Schöler, Nathalie (BioMed Central, 2011)
MicroRNAs are post-transcriptional regulators that are involved in many physiological and pathophysiological conditions. A recent study compared the expression profiles of hundreds of blood-borne microRNAs across a variety of nonmalignant and malignant diseases to identify disease-specific expression patterns. The resulting microRNA expression data could be used to discriminate disease samples with a high level of accuracy, demonstrating the potential for using microRNA signatures for the blood-based diagnosis of disease.